Nomogram predicts CR-POPF in open central pancreatectomy patients with benign or low-grade malignant pancreatic neoplasms - Ouyang, Liu; Liu, Ren-dong; Ren, Yi-wei; Nie, Gang; He, Tian-lin; Li, Gang; Zhou, Ying-qi; Huang, Zhi-ping; Zhang, Yi-jie; Hu, Xian-gui; Jin, Gang (Frontiers in Oncology, 2022)
Objectives: To establish a predictive nomogram of clinically relevant postoperative pancreatic fistula (CR-POPF) for patients who underwent central pancreatectomy (CP) for benign or low-grade malignant pancreatic neoplasms. Background: CP has become a standard surgical procedure for benign and low-grade malignant pancreatic neoplasms in the neck and body of the pancreas. Several studies have reported a higher incidence of CR-POPF after CP than standard pancreaticoduodenectomy (PD) and distal pancreatectomy (DP), but the predictive nomogram of CR-POPF for CP has not been well established until now. Methods: Patients who underwent CP for benign or low-grade malignant pancreatic neoplasms in the department of the Hepatobiliary and Pancreatic (HBP) surgery of Shanghai Changhai Hospital affiliated to Naval Medical University between January 01, 2009 and December 31,2020 were enrolled. Pre-, intra- and post- operative parameter were analyzed retrospectively. Results: Among the 194 patients included in this study, there were 60 men and 134 women, with a median age of 52 years old (range 21~85 years). 84 patients (43.3%) were overweight (BMI＞23.0 Kg/m2),and 14 patients (7.2%) were obesity (BMI＞28.0 Kg/m2). The most common pathologic diagnosis was serous cystic neoplasm (32.5%), followed by solid pseudopapillary neoplasm (22.2%), pancreatic neuroendocrine tumor (20.1%), intraductal papillary mucinous neoplasm (18.0%), and mucinous cystic neoplasm (5.2%). All the patients had soft pancreatic texture. The diameter of the main pancreatic duct in 158 patients (81.4%) were≤0.3cm, only 12 patients (6.2%) had main pancreatic duct≥0.5cm in diameter. We used stapler (57.7%) and hand-sewn closure (42.3%) method to deal with the pancreatic remnant. The pancreatic anastomosis techniques were duct to mucosa pancreaticojejunostomy (PJ)-interrupted suture (47.4%), duct to mucosa PJ-continuous suture (43.3%), duct to mucosa “HO” half-purse binding PJ (5.2%), and invaginating pancreaticogastrostomy (4.1%). The incidence of CR-POPF, surgical site infection, postpancreatectomy hemorrhage, and delayed gastric emptying were 45.9%, 28.9%, 7.7%, and 2.1%, respectively. Obesity and pancreatic anastomosis technique were independent risk factors of CR-POPF, with a concordance index of 0.675 and an Area Under Curve of 0.678. Conclusions: This novel nomogram constructed by obesity and pancreatic anastomosis technique showed moderate predictive performance of CR-POPF for CP.